Formalne lastnosti razpravnih besedil v Slavistični reviji (1991-2002) - Novak, Nina (Slavistična revija, 2003)
The article analyzes 12 volumes of Slavistična revija, published between 1991 and 2002. In addition to statistical data, such as the number of linguistic and literary articles, classification of authors into Slovene and foreign, the types of footnotes, reference lists, the language of summaries, the division of the part of the journal dedicated to writing other than articles - the article also provides a more detailed content analysis of abstracts and their typology.
Keywords: analiza; izvlečki; serijske publikacije; Slavistična revija; tematika; tiplogija